Characterizing responses to CFTR-modulating drugs using rectal organoids derived from subjects with cystic fibrosis - Dekkers, Johanna F; Berkers, Gitte; Kruisselbrink, Evelien; Vonk, Annelotte; de Jonge, Hugo R; Janssens, Hettie M; Bronsveld, Inez; van de Graaf, Eduard A; Nieuwenhuis, Edward E S; Houwen, Roderick H J; Vleggaar, Frank P; Escher, Johanna C; et al. (Science translational medicine, 2016)
Identifying subjects with cystic fibrosis (CF) who may benefit from cystic fibrosis transmembrane conductance regulator (CFTR)-modulating drugs is time-consuming, costly, and especially challenging for individuals with rare uncharacterized CFTR mutations. We studied CFTR function and responses to two drugs-the prototypical CFTR potentiator VX-770 (ivacaftor/KALYDECO) and the CFTR corrector VX-809 (lumacaftor)-in organoid cultures derived from the rectal epithelia of subjects with CF, who expressed a broad range of CFTR mutations. We observed that CFTR residual function and responses to drug therapy depended on both the CFTR mutation and the genetic background of the subjects. In vitro drug responses in rectal organoids positively correlated with published outcome data from clinical trials with VX-809 and VX-770, allowing us to predict from preclinical data the potential for CF patients carrying rare CFTR mutations to respond to drug therapy. We demonstrated proof of principle by selecting two subjects expressing an uncharacterized rare CFTR genotype (G1249R/F508del) who showed clinical responses to treatment with ivacaftor and one subject (F508del/R347P) who showed a limited response to drug therapy both in vitro and in vivo. These data suggest that in vitro measurements of CFTR function in patient-derived rectal organoids may be useful for identifying subjects who would benefit from CFTR-correcting treatment, independent of their CFTR mutation.